Assessment of oligoclonal bands in cerebrospinal fluid and serum of dogs with meningoencephalitis of unknown origin. - Julia K Prümmer; Veronika M Stein; Eliane Marti; Andreas Lutterotti; Ilijas Jelcic; Gertraud Schüpbach-Regula; Thorsten Buch; Arianna Maiolini (PLoS ONE, 2023)
Background Meningoencephalitis of unknown origin (MUO) is an inflammatory disease of the canine central nervous system (CNS) that shares several features with multiple sclerosis (MS) in humans. In approximately 95% of MS patients, ≥ two immunoglobulin G (IgG) oligoclonal bands (OCBs) are detectable exclusively in the cerebrospinal fluid (CSF). Hypothesis/objectives To investigate OCBs in CSF and serum in dogs affected by MUO, intervertebral disc disease (IVDD), idiopathic epilepsy (IE), intracranial neoplasia (IN), steroid-responsive meningitis-arteritis (SRMA), and diseases outside the CNS. We hypothesize that the highest prevalence of CSF-specific OCBs (≥ two OCBs uniquely in the CSF) would be found in dogs affected by MUO. Animals Client-owned dogs (n = 121) presented to the neurology service due to neurological deficits. Methods Prospective study. Measurement of IgG concentration in CSF and serum via a canine IgG ELISA kit. OCB detection via isoelectric focusing (IEF) and immunoblot. Results Presence of CSF-specific OCBs was significantly higher in dogs with MUO (57%) compared to 22% in IN, 6% in IE, 15% in SRMA, 13% in IVDD, and 0% in the non-CNS group (p < .001). Dogs with MUO were 9.9 times more likely to show CSF-specific OCBs than all other diseases together (95% confidence interval, 3.7-26.4; p < .001). Conclusions and clinical importance MUO showed the highest prevalence of CSF-specific OCBs, indicating an inflammatory B cell response. Future studies are needed to evaluate the prevalence in the specific MUO subtypes and a possible similarity with human MS.